Institutional ownership and market-based performance indicators: Utilizing generalized least square estimation technique - Che Ahmad, Ayoib; Jusoh, Mohd Abdullah (Elsevier Ltd., 2014)
This study investigates the relationship between institutional ownership and company performance of public listed companies in Malaysia.Three years panel data of 730 Malaysian public listed companies were examined.The results showed that institutional ownership had positive and significant relationship with Tobin's Q and share price.Therefore, the involvement of institutional investor in monitoring and controlling activities reduced agency conflict and enhanced corporate performance in the emerging economy.